Synthesis of 3-amino-2,3-dideoxysugars with their applications and total synthesis of pyridone alkaloids - Ding, Feiqing (2013)
Firstly, a highly stereoselective tandem hydroamination/glycosylation on glycal scaffold has been developed to form 3-amino-2,3-dideoxysugars in a one-pot manner. Based on the developed methodology, broad applications were introduced in glycochemistry. Secondly, a combination of convergent and divergent total synthesis (DTS) approach presented herein sets stage for an iterative introduction of R1 chain among structurally diverse pyridone alkaloids (see scheme). Interestingly, among the six tumor cell lines conducted for cell proliferation, Jurkat T-cells was discovered with potent and apoptotic inhibitory activites. Thirdly, a diverted total synthesis (DTS) approach to the total syntheses of pyridone alkaloids N-deoxymilitarninone A and Torrubiellone Bhas been developed. The common intermediate was first assembled by dual Directed ortho Metalation (DoM) process using MOM as Directed Metalation Groups (DMGs).